2016
DOI: 10.1002/uog.15754
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with single‐nucleotide polymorphism‐based non‐invasive prenatal screening for 22q11.2 deletion syndrome

Abstract: ObjectivesTo evaluate the performance of a single‐nucleotide polymorphism (SNP)‐based non‐invasive prenatal test (NIPT) for the detection of fetal 22q11.2 deletion syndrome in clinical practice, assess clinical follow‐up and review patient choices for women with high‐risk results.MethodsIn this study, 21 948 samples were submitted for screening for 22q11.2 deletion syndrome using a SNP‐based NIPT and subsequently evaluated. Follow‐up was conducted for all cases with a high‐risk result.ResultsNinety‐five cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
142
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(151 citation statements)
references
References 28 publications
8
142
1
Order By: Relevance
“…Reports from reference laboratories have been broadly consistent with the estimates of detection rates (DRs) and false-positive rates (FPRs) established in these trials [2][3][4][5][6]. Additionally, both proof of principle [7][8][9] and data from reference laboratories [10,11] have indicated that screening is possible for select sets of microdeletion syndromes.…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…Reports from reference laboratories have been broadly consistent with the estimates of detection rates (DRs) and false-positive rates (FPRs) established in these trials [2][3][4][5][6]. Additionally, both proof of principle [7][8][9] and data from reference laboratories [10,11] have indicated that screening is possible for select sets of microdeletion syndromes.…”
Section: Introductionsupporting
confidence: 52%
“…A major difficulty in clinical experience studies has been that confirmation studies have been substantially incomplete [2][3][4]11] and this study also has incomplete followup data. Low follow-up rates can be attributable to multiple factors including referral of confirmatory testing to different laboratories and incomplete documentation.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations